Rumah Makan Padang Sebuah Narasi Pertunjukan Budaya; Studi Kasus Rumah Makan Padang Simpang Raya - Ismar, Madia Patra (Sekolah Pascasarjana Institut Kesenian Jakarta, 2018)
This research is to explore the cultural values of the Minangkabau people in the cultural narrative of the Padang Simpang Raya restaurant. Rumah Makan Padang Simpang Raya is a migratory representation of Minangkabau people who reproduce their culture in urban areas. This phenomenon is seen using the views of several experts to express diacritic writing of values in a narrative of cultural performances. The discussion about cultural performances as a display of social relations, edible and non edible, gesture and artistic stylization, structuring, silent resistance, Minangkabau tradition will be discussed. Anthony Giddens views about civilization will be touched upon and this writers argument of the rumah makan padang as a strength on cultural diplomacy is to be explored an to open the awareness that Western civilization is not the only one, will close this paper. Penelitian ini adalah untuk menelusuri nilai-nilai budaya masyarakat Minangkabau dalam narasi budaya rumah makan padang Simpang Raya. Rumah Makan Padang Simpang Raya adalah representasi perantauan masyarakat Minangkabau yang mereproduksi budayanya di perkotaan. Fenomena ini dilihat menggunakan pandangan beberapa ahli untuk mengungkapkan diacritic writing nilai-nilai dalam suatu narasi pertunjukan budaya. Diskusi mengenai pertunjukan budaya sebagai display relasi sosial, edible dan non edible, gesture dan stilisasi artistiknya, strukturasi, silent resistance, tradisi Minangkabau akan menjadi bahasan. Kegelisahan Anthony Giddens mengenai peradaban akan disentuh dan tawaran rumah makan padang sebagai cultural diplomasi untuk membuka kesadaran bahwa peradaban Barat bukan hanya satu-satunya, akan menutup tulisan ini.